Canadian Thoracic Society Asthma Management Continuum – 2010 Consensus Summary for Children Six Years of Age and Over, and Adults - M Diane Lougheed; Catherine Lemière; Sharon D Dell; Francine M Ducharme; J Mark FitzGerald; Richard Leigh; Chris Licskai; Brian H Rowe; Dennis Bowie; Allan Becker; Louis-Philippe Boulet (Canadian Respiratory Journal)
BACKGROUND/OBJECTIVE: To integrate new evidence into the Canadian Asthma Management Continuum diagram, encompassing both pediatric and adult asthma.